Watertight papers to skim through - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Managing water equitably, efficiently and sustainably for agricultural and rural development in sub-Saharan Africa and the Caribbean Synthesis Report on the CTA Seminar, Cordoba, Spain, 20-25 September 1999, CTA, 2001. 36 pp. ISBN 92 9081 2524 CTA num